Strategy For Developing The Transformation of Traditional Farmers in Samarinda Towards Future Agriculture - F. Silvi Dwi Mentari; Yuanita; Nur Hidayat; Daryono; Zainal Abidin; Roby; Ita Merni Patulak Merni; Zahrotul Isti'anah (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2025)
The knowledge of farming methods and various traditional agricultural tools owned by the ancestors of the people of East Kalimantan has been passed down to their descendants, remaining simple and used by a group of people from generation to generation, forming part of their technological system, according to their cultural conceptions. However, the current agricultural transformation in Samarinda shows a clear shift from traditional to modern farming systems, evident in the application of modern technology in agricultural activities. This study examines the transformation process, its driving factors, socio-economic impacts, and challenges and development strategies. Data were collected through literature review and interviews with local farmers. The results indicate that modern agriculture increases productivity and work efficiency, attracts younger generations, and supports food security in the region. However, limited land and access to technology are key challenges. The study concludes that agricultural modernization in Samarinda must be supported by inclusive policies that integrate technology, strengthen farmer institutions, and empower young people.